General anesthesia with spontaneous breathing and laryngeal mask airway intubation combined with peripheral nerve block in orthopedic surgery: a retrospective study - Tu, Jiahui; Peng, Piao; Xiong, Zhaodong (Frontiers in Medicine, 2025)
ObjectivesTo investigate the effect of general anesthesia with spontaneous breathing laryngeal mask airway (LMA) intubation combined with a peripheral nerve block (PNB) in orthopedic surgery through a retrospective study.MethodsData from 160 adult patients (American Society of Anesthesiologists grade 1–3) who underwent elective orthopedic surgery under general anesthesia with LMA intubation combined with PNB were retrospectively analyzed. All patients received ultrasound-guided PNB before general anesthesia. Among them, 78 patients were assigned to the spontaneous breathing group and 82 patients to the pressure-controlled ventilation group. The parameters compared included baseline characteristics, perioperative anesthetic drug dosages, anesthesia recovery time, adverse events during recovery, numerical rating scale score at 2 h postoperatively, postoperative pulmonary complications, hospitalization costs, and length of stay.ResultsBoth groups successfully completed the surgeries. Compared to the pressure-controlled ventilation group, the spontaneous breathing group exhibited significantly lower doses of fentanyl and rocuronium bromide (p < 0.001), shorter length of stay (p = 0.047), reduced incidence of postoperative hypertension in the post-anesthesia care unit (p < 0.001), and lower anesthesia costs (p < 0.001) and total hospitalization costs (p = 0.001). No statistically significant differences were observed between the two groups in baseline characteristics, anesthesia recovery time, incidence of postoperative hypoxemia or hypotension in the post-anesthesia care unit, numerical rating score at 2 h postoperatively, incidence of postoperative pulmonary complications, or surgical costs.ConclusionGeneral anesthesia with spontaneous breathing LMA intubation combined with PNB is safe and feasible for elective orthopedic surgeries in adults. This approach is beneficial in shortening the length of stay and reducing hospitalization costs.